Portugal-IPES-The 29th Annual Meeting of the IPES-International Police Executive Symposium, Vienna, Austria, 2018 - Bandeira, Gonçalo S. de Melo (2019)
PORTUGAL_IPES_Prof. Dr. M. Gonçalo S. de Mello Bandeira has an LLD in Juridical Criminal Sciences by Coimbra University Law Faculty since 2009 and Master in Juridical Criminal Sciences by the Portuguese Catholic University Law Faculty since 2003. Law degree Coimbra University Law Faculty. Adjunct Professor in Public Law at Polytechnic Institute of Cávado and Ave (IPCA), Management School. An integrated researcher at the Centre of Studies in European Union Law (CEDU). He has collaborated at a Masters Degree level with Minho University Law School, as well as with other Universities.